2014
DOI: 10.1080/21642583.2014.996301
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and model predictive control of dividing wall column for separation of Benzene–Toluene-o-Xylene

Abstract: In this paper, dividing wall column (DWC) has been chosen for a BTX (Benzene-Toluene-o-Xylene) system. A MATLAB ® program has been written for nonlinear unsteady-state DWC, which is used in Simulink environment for control of the system by Model Predictive Control (MPC). Compositions of the three products (benzene, toluene, and o-xylene) are indirectly controlled by controlling the corresponding temperatures of the respective tray due to requirement of online analyzer. The temperature of uppermost tray in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…To control the dividing wall column is the big challenge for the control engineers due to its high dynamics. Conventional controller like PID is not performed well in comparison to the advanced controller which was shown by the authors in their research [3]. Artificial neural network has been applied on dividing wall column for controlling the tray temperatures that is based on predictive technique.…”
Section: Introductionmentioning
confidence: 99%
“…To control the dividing wall column is the big challenge for the control engineers due to its high dynamics. Conventional controller like PID is not performed well in comparison to the advanced controller which was shown by the authors in their research [3]. Artificial neural network has been applied on dividing wall column for controlling the tray temperatures that is based on predictive technique.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies have also been proposed to control DWC by measuring impurities in the product streams instead of the purities of the desired products 15. Recently, advanced control strategies for the control of thermally coupled systems have been proposed, such as model predictive control 16–18 and fuzzy control 19, among others. Also recently, Ramírez‐Corona et al 20 presented a control analysis of thermally coupled distillation columns, considering not only the isolated equipment but the interactions with whole processes.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive distillation is the combination of both separation and reaction in one unit [1][2][3][4]. It has been used in a small number of industrial applications for many years, but the last two decades has shown an increase in both research and applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in a small number of industrial applications for many years, but the last two decades has shown an increase in both research and applications. Distillation is the most desirable process for the separation of multi-component liquid mixture [4]. Combining reaction with distillation as is done in reactive distillation offers significant economic benefits, especially for reversible reactions.…”
Section: Introductionmentioning
confidence: 99%